Model development for flash boiling spray and validations with isooctane, hexane, ethanol and their binary mixtures. (1st August 2022) - Gao, Suya; Yan, Junhao; Lee, Timothy H.; Lee, Chia-Fon
Highlights: Comprehensive atomization model focused on the process of flash boiling condition. A unified breakup model was considered for both aerodynamic and flash boiling. Morphologies of both single- and binary-component sprays were predicted. Droplet size distribution was well captured under all tested conditions. Collasping was found when r p less than 0.3 for all sprays regardless of fuel types. Abstract: The main objective of this study is to develop a comprehensive model for spray atomization under the consideration of flash boiling, which includes nucleation, bubble growth, and droplet breakup. Although flash boiling has been previously studied, there is still no well-established analytical and numerical model of their mechanisms, or general guidelines on the implementation of this atomization strategy. In this study, detailed formulations are elaborated for the unified spray atomization model under both non-flash and flash boiling conditions. Next, the model was implemented into CFD software and 3-D simulations were performed for model validations. Two fuel blends are tested: ethanol-isooctane blends and hexane-isooctane blends. Simulation results were compared with the experimental measurements conducted using two methodologies, DBI (Diffuse Backlight Imaging) system for spray images captured by a high-speed camera, and a PDA (Phase Doppler Anemometry) system for droplet size measurement during the spray injection process. It was found that the current flash boiling model can accurately capture the spray characteristics under different environment conditions, such as the spray plume interactions and liquid penetration. The averaged Sauter mean diameter (SMD) calculations match the measurement sufficiently well. The spray structures for both single- and multi-component fuels during the injection process are well represented by current model.